A NOVEL DOMESTIC HYGIENIC POWDER FOR CLEANING REMOVABLE DENTURES: CLINICAL AND MICROBIOLOGICAL EVALUATION (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background: Denture surfaces promote microbial adhesion and biofilm formation, increasing the risk of inflammatory oral diseases. Objective: To evaluate the clinical and microbiological effectiveness of a newly developed domestic hygienic powder for cleaning removable dentures compared with mechanical cleaning and Corega Bio Formula tablets. Methods: A comparative clinical study was conducted among patients wearing acrylic and nylon removable dentures. Microbial samples were collected at baseline, after 1 month, and after 3 months. Results: The novel hygienic powder demonstrated the most pronounced reduction in microbial load, including Streptococcus spp. and Candida spp. Conclusion: The developed powder provides superior antimicrobial efficacy and supports its implementation in prosthetic practice.
Keywords: Removable dentures; denture hygiene; biofilm; Candida spp.; antimicrobial activity; prosthetic dentistry.